Association between Interleukin-10 Gene Polymorphisms and Behcet’s Disease Susceptibility: Evidence from a Meta-Analysis - Xue-Feng Li; Zhi-Zhen Huang; Yuan-Yuan Hu; Yu-Ming Niu; Jun-Wei Cai (Journal of Immunology Research)
Epidemiological studies have demonstrated that interleukin-10 (IL-10) polymorphisms may be associated with the development of Behcet’s disease (BD). However, the published results were inconsistent. Therefore, this meta-analysis was conducted to derive a more precise relationship between IL-10 polymorphisms and BD susceptibility. Online databases (PubMed, Embase, Science Citation Index (SCI), CNKI, and WanFang) were searched to identify eligible studies. Odds ratio (OR) and a 95% confidence interval (CI) were applied to assess the relationship strength between IL-10 -1082A>G (rs1800896), -819T>C (rs1800871), and -592A>C (rs1800872) polymorphisms and BD susceptibility. Publication bias, sensitivity, and cumulative analyses were conducted to measure the robustness of our findings. Finally, fifteen articles (36 independent case-control studies) involving 5,971 patients and 8,913 controls were included. Overall, significant associations between -819T>C polymorphisms and BD risk were observed in the total population (C vs. T: OR=0.72, 95%CI=0.67‐0.77, P<0.01, I2=36.6%; TC vs. TT: OR=0.73, 95%CI=0.66‐0.80, P<0.01, I2=23.0%; CC vs. TT: OR=0.52, 95%CI=0.39‐0.70, P<0.01, I2=53.7%; TC+CC vs. TT: OR=0.67, 95%CI=0.61‐0.71, P<0.01, I2=22.1%; and CC vs. TT+TC: OR=0.66, 95%CI=0.53‐0.82, P<0.01, I2=57.8%). Moreover, the IL-10 -592 A>C polymorphism and the ACC haplotype exhibited a significant, protective effect against BD susceptibility. In summary, our meta-analysis suggested that IL-10 gene polymorphisms may play a salient role for BD development.